2021
DOI: 10.3906/biy-2007-58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bradykinin on proliferation, apoptosis, and cycle of glomerular mesangial cells via the TGF-β1/Smad signaling pathway

Abstract: We aimed to assess the effects of bradykinin (BK) on the proliferation, apoptosis, and cycle of glomerular mesangial cells via the transforming growth factor-β 1 (TGF-β1)/Smad signaling pathway. Rat glomerular mesangial cells, HBZY-1, were divided into normal group (untreated), model group (5 ng/L TGF-β1), BK group (5 ng/L TGF-β1 + 1 ng/L BK), and inhibitor group [5 ng/L TGF-β1 + 1 ng/L LY2109761 (TGF-β1-specific inhibitor)]. The cell proliferation, cycle, apoptosis, expression of type I collagen (Col-1), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These results indicated that CAV-1 was involved in redoxosomes signaling and may be a novel therapeutic target of DKD. The TGF-β1/SMAD signaling has an important role in renal fibrosis, the activation of which is crucial to the formation of the ECM ( 32 , 33 ). The present results indicated that CAV-1 could also activate TGF-β1/SMAD signaling, which may result in ECM accumulation in MCs under hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that CAV-1 was involved in redoxosomes signaling and may be a novel therapeutic target of DKD. The TGF-β1/SMAD signaling has an important role in renal fibrosis, the activation of which is crucial to the formation of the ECM ( 32 , 33 ). The present results indicated that CAV-1 could also activate TGF-β1/SMAD signaling, which may result in ECM accumulation in MCs under hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%